The precursors of monastic medicine at the beginning of the Middle Ages - Supady, Jerzy (Health Promotion & Physical Activity, 2019)
The collapse of the ancient civilization was like a disaster which had an impact on all spheres of life. The Roman Church was the institution which survived the historical annihilation. Therefore, the ones who significantly contributed to the preservation of the remnants of the former world, inter alia ancient manuscripts, and the development of new science based on an ancient knowledge, including medical science, were the members of the clergy, mainly monks and friars.